2017
DOI: 10.1039/c7sc01219e
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal thallium halide nanocrystals with reasonable luminescence, carrier mobility and diffusion length

Abstract: Colloidal TlI and TlBr nanocrystals are prepared, which show violet-blue luminescence, high carrier mobility and long diffusion lengths thus suggesting the suppression of deep-trap states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 68 publications
0
27
1
Order By: Relevance
“…There is also an Urbach tail extending to longer wavelength, which could indicate the presence of silver‐thallium antisite defects. We could not determine if the nanocrystals emitted light because of the strong overlapping photoluminescence signal from oleylamine and oleic acid in the band‐edge spectral region …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also an Urbach tail extending to longer wavelength, which could indicate the presence of silver‐thallium antisite defects. We could not determine if the nanocrystals emitted light because of the strong overlapping photoluminescence signal from oleylamine and oleic acid in the band‐edge spectral region …”
Section: Resultsmentioning
confidence: 99%
“…Because of the health risk posed by Tl‐exposure, device layer deposition with nanocrystals might prove safer than using solutions of Tl in dimethylsulfoxide (DMSO) or n‐methylpyridine (NMP) . As of now, there are only a few examples of thallium halide nanocrystal synthesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The groups of Xiong from Nanyang Technological University and Irvine from the University of St Andrews discussed the different synthesis approaches and growth mechanisms, as well as various applications, of metal halide perovskite nanomaterials and nanoporous perovskite metal oxides, respectively; 12,13 the synthesis of one-dimensional organicinorganic hybrid perovskite micro/ nanostructures, reported by Yan's group, efficiently enhanced the water stability and luminescence properties, thus extending their applications to sensing and photonic communication micro-devices; 14 Wu's group suggested that tetracenes could drive single and even multi-electron photochemical reactions; 15 Moser and coworkers investigated the charge transfer dynamics at the surface of nanoparticles; 16 Nag's and Mandal's group discovered that colloidal thallium halide nanocrystals possessed high effective carrier mobility, long diffusion length and reasonably high luminescence. 17 Perovskites are now considered as the most promising optoelectronic materials for future applications. We hope this themed collection will showcase the latest developments in perovskites and shed some light on future research trends for their applications.…”
mentioning
confidence: 99%
“…[1] Subsequently,s earch for Pb-free perovskites as alternative optoelectronic materials has begun, because of both scientific curiosity and practical issues,s uch as improvement in device stability along with reduction in toxicity. [2] Among colloidal Pb-free NCs explored so far, CsSnX 3 (X = Cl, Br, I) perovskites NCs suffers from poor stability, [3] Cs 2 SnX 6 NCs have a0Dstructure detrimental for charge-transport, [4] TlX NCs [5] and (CH 3 NH 3 ) 3 Bi 2 X 9 NCs [6] exhibit wide band gaps in the UV region, and Cs 3 Bi 2 I 9 NCs have a0 Ds tructure with large effective masses of charge carriers (Table S1 and S2 in the Supporting Information). [7] To our knowledge,t here is no report of any colloidal Pb-free perovskite NCs with suitable properties for visible-light optoelectronics.T herefore,h erein we report the preparation of colloidal Cs 3 Sb 2 I 9 and Rb 3 Sb 2 I 9 NCs,a long with their optical properties including luminescence and ultrafast carrier dynamics.…”
mentioning
confidence: 99%